Pengaruh Fasilitas Belajar terhadap Hasil Belajar Mata Pelajaran IPS - Ach Nurhamid Awalluddin; Ahmad Afan Zaini (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2023)
Learning facilities are important for the implementation of the learning process and learning, this research was conducted to determine the effect of learning facilities on student learning outcomes. The method used is quantitative, descriptive type, where in data collection a questionnaire instrument is used to collect data about learning facilities and documentation is used to collect data about learning outcomes. The results of the research show that there is no influence between learning facilities on the learning outcomes of junior high school plus al-kautsar students in the city of Malang.